2019
DOI: 10.1016/j.metabol.2019.153947
|View full text |Cite
|
Sign up to set email alerts
|

AKR1D1 is a novel regulator of metabolic phenotype in human hepatocytes and is dysregulated in non-alcoholic fatty liver disease

Abstract: ObjectiveNon-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome. Steroid hormones and bile acids are potent regulators of hepatic carbohydrate and lipid metabolism. Steroid 5β-reductase (AKR1D1) is highly expressed in human liver where it inactivates steroid hormones and catalyzes a fundamental step in bile acid synthesis.MethodsHuman liver biopsies were obtained from 34 obese patients and AKR1D1 mRNA expression levels were measured using qPCR. Genetic manipulation of AKR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 69 publications
(62 reference statements)
2
59
0
Order By: Relevance
“…Recently, changes in the expression patterns of transcriptional regulators and downstream target genes have been associated with the development and progression of chronic liver diseases such as NAFLD [65,66], non-alcoholic steatohepatitis (NASH) [67], fibrosis [15] and human hepatocellular carcinoma (HCC) [54]. Here we show that our methodology is highly sensitive to detect those gene markers in the nuclear transcriptome ( Fig.…”
Section: Snrna-seq2 Uncovers Transcription Factors and Rate Limiting mentioning
confidence: 62%
See 1 more Smart Citation
“…Recently, changes in the expression patterns of transcriptional regulators and downstream target genes have been associated with the development and progression of chronic liver diseases such as NAFLD [65,66], non-alcoholic steatohepatitis (NASH) [67], fibrosis [15] and human hepatocellular carcinoma (HCC) [54]. Here we show that our methodology is highly sensitive to detect those gene markers in the nuclear transcriptome ( Fig.…”
Section: Snrna-seq2 Uncovers Transcription Factors and Rate Limiting mentioning
confidence: 62%
“…2E-F). In particular, dysregulation of Akr1d1 has been associated with human NAFLD [66], and upregulation of Wwtr1 (also known as TAZ) in human and murine NASH liver [68]. Furthermore, Tead1 has been proposed as a marker of NASH in murine mouse models [69].…”
Section: Snrna-seq2 Uncovers Transcription Factors and Rate Limiting mentioning
confidence: 99%
“…4C). Relevant to lipid metabolism, we found upregulation of three genes related to cholesterol transport (NR0B2 39 , APOA4 40 , and APOA1 41 ) and another seven genes related to cholesterol biosynthesis (MVK, MVD, HMGCS1 42 , FDFT1 43 , HMGCR 44 , FDPS 45 , CYP51A1 46 ), along with downregulation of AKR1D1 47 , involved in cholesterol catabolism (Fig. 3a).…”
Section: Ethanol-induced Steatosis In the Liver-chipmentioning
confidence: 89%
“…In addition, they are used in combination with anti-cancer agents to reduce the genotoxic side effects of chemotherapy treatment, including nausea and vomiting (Collins et al 2007; Buxant et al 2015). Pro-longed use of synthetic glucocorticoids is however associated with adverse metabolic effects including obesity, insulin resistance, and non-alcoholic fatty liver disease (NAFLD) (Woods et al 2015), and decreased AKR1D1 expression has been recently shown in patients with type 2 diabetes and NAFLD (Valanejad et al 2018; Nikolaou et al 2019b). Our study indicates that AKR1D1-002 is the predominant functional variant in human liver; alterations in AKR1D1-002 expression and activity may therefore contribute to the adverse metabolic impact of exogenous glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%